EVOLVING A CO-LOCATED PROCESS MODEL FOR GLOBALLY DISTRIBUTED SOFTWARE DEVELOPMENT - Sundell, Magnus (My University, 2010)
The topic of the thesis is software process improvement for distributed software development. Its purpose is to derive a process model addressing the needs of this multi-site work. The scope is limited to proposing improvements to an existing software process. Analysis of efficiency, weaknesses or strengths of the proposed process is not within the scope of this thesis. Observations from a project case study in a Finnish industrial enterprise revealed the organization’s weaknesses. The case study analyzed created documentation, collaboration and interaction in weekly meetings as well as semi-structured interviews with project members. These results are supplemented by a literature review on multi-site software development challenges and solutions. Based on the combined findings, a proposal for an improved software process is derived. Significant observations include lacking knowledge transfer, poor documentation quality and issues in communication between teams. The improved process emphasizes knowledge and documentation management, clarity in assignment of roles and greater effort in planning of verification activities. It can be concluded that multi-site software development should be carefully considered and requires mature processes to achieve satisfactory performance. Software process improvement is necessary for enabling prosperous global software development collaboration.
Keywords: software process; software process improvement; global software development; distributed software development; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Tietotekniikan koulutusohjelma (DI)|